The impact of tariff diversity on broadband penetration—An empirical analysis. Issue 8 (August 2016) - Haucap, Justus; Heimeshoff, Ulrich; Lange, Mirjam R.J.
Abstract: This paper provides an empirical analysis how tariff diversity affects fixed broadband penetration. To measure tariff diversity on a country-level a detailed data set comprising over 1000 fixed-line broadband tariffs is used. An instrumental variable approach is applied to estimate demand, controlling for various industry and socio-economic factors. Our results indicate that service-related and socio-economic factors affect broadband demand the most. An increase in tariff diversity provides a significant impetus to broadband adoption. A positive relationship is indicative of the importance of innovative pricing schemes in expediting the ascent of broadband internet access. Abstract : Highlights: Impact of tariff diversity on broadband penetration. Country-level data base, comprising over 1000 fixed-line broadband tariffs. Demand estimation using instrumental variables and various industry and socio-economic factors as controls. Significant positive effect of tariff diversity on broadband adoption. Shows the importance of innovative pricing schemes in expediting the ascent of broadband internet access.